2020
DOI: 10.1016/j.ekir.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Difelikefalin for Chronic Pruritus in Hemodialysis Patients

Abstract: Introduction: There is an unmet medical need for pruritus associated with chronic kidney disease, a distressing complication characterized by generalized and persistent itch affecting 20% to 40% of patients undergoing hemodialysis. Here we report the results of a phase 2 trial evaluating the efficacy and safety of a novel peripherally restricted kappa opioid receptor agonist, difelikefalin, in adult patients undergoing hemodialysis with pruritus. Methods: In this study, 174 hemodialysis patients with moderate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 29 publications
5
70
0
Order By: Relevance
“…The 2 doses of difelikefalin in the current study are 2 to 10 times higher than the doses assessed in the phase 3 study of difelikefalin in patients with CKD-aP. 18,19 In previous clinical studies, bolus IV doses of Accepted Article difelikefalin 0.5 to 40.0 mcg/kg have been administered to healthy volunteers (unpublished data) or patients with chronic kidney disease without any indication of compromised respiratory safety compared with placebo. 18,19 SpO 2 is less sensitive to changes in acute respiratory events than the ETCO 2 parameter.…”
Section: Discussionmentioning
confidence: 91%
“…The 2 doses of difelikefalin in the current study are 2 to 10 times higher than the doses assessed in the phase 3 study of difelikefalin in patients with CKD-aP. 18,19 In previous clinical studies, bolus IV doses of Accepted Article difelikefalin 0.5 to 40.0 mcg/kg have been administered to healthy volunteers (unpublished data) or patients with chronic kidney disease without any indication of compromised respiratory safety compared with placebo. 18,19 SpO 2 is less sensitive to changes in acute respiratory events than the ETCO 2 parameter.…”
Section: Discussionmentioning
confidence: 91%
“…This study demonstrated the antipruritic effects of the selective -opioid receptor agonist, difelikefalin, with a significant reduction of itch intensity and an improvement of itch-related quality of life (QoL) over placebo. 5 Itch intensity and QoL scores were collected over an 8-week treatment period. 5 The Patient Global Impression of Change (PGI-C), with 7 categories ranging from ''very much improved'' to ''very much worse,'' Patient Global Impression of Worst Itch Severity (PGI-S), with values from 0 (none) to 4 (very severe), and the Skindex-10 and 5-D itch QoL questionnaires were selected as anchor variables in the present analysis (Supplemental Figs 2-5).…”
mentioning
confidence: 99%
“…Another compound currently receiving growing interest, difelikefalin (CR845), is selective towards peripheral kappa-opioid receptors in the skin as it is not able to cross the blood-brain barrier [45]. In a phase II randomized trial among subjects with UP, difelikefalin was administered intravenously (after a [46,47]. Notably, the beneficial WI-NRS response of difelikefalin started to unveil after 1 week of treatment.…”
Section: Difelikefalinmentioning
confidence: 99%
“…Another compound currently receiving growing interest, difelikefalin (CR845), is selective towards peripheral kappa-opioid receptors in the skin as it is not able to cross the blood–brain barrier [ 45 ]. In a phase II randomized trial among subjects with UP, difelikefalin was administered intravenously (after a hemodialysis session) thrice weekly for 8 weeks in doses of 0.5, 1.0 or 1.5 mg/kg to 44, 42 and 44 patients, respectively, while 45 patients received placebo [ 46 ]. At week 8, patients receiving difelikefalin were significantly more prone to experience alleviation of pruritus (at least − 3 points in the WI-NRS) when compared with placebo (59% vs. 29%; p = 0.001), as well as significant improvement in itch-related QoL.…”
Section: Opioid Receptor Agonists and Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation